Hotel selection attributes among mature travellers at Redang Island / Jazira Anuar...[et al.] - Anuar, Jazira; Musa, Mushaireen; Khalid, Khazainah; Anderson, Ngelambong (Faculty of Hotel and Management, Universiti Teknologi MARA, Selangor, Kampus Puncak Alam Campus, 2017)
Mature travellers had been contemplated as the major contributor to the hotel’s revenue for many resorts. Most of the mature travellers have a freedom to travel due to less family commitment, more flexible with their travelling time, more discretionary income and have ample time to make decision inchoosing a final hotel to stay. This research paper looks into the selection attributes for mature travellers focusing on travelling to Redang Island. An investigation on the traveller’s preferences among mature travellers was carried out through in-depth interviews with 32 mature travellers staying in hotels/resorts in Redang. Findings suggest that though this mature traveller is evolving, many hotel operators tend to overlook on the importance of this market segmentation. Findings also suggest that hotels should be more proactive in their response concerning the selection attributes for mature travellers.